Mn-based hard magnets with small saturation magnetization and low spin relaxation for spintronics. (June 2016) - Mizukami, S.; Sakuma, A.; Sugihara, A.; Suzuki, K.Z.; Ranjbar, R.
Abstract: The pursuit of high saturation magnetization is an important area of hard magnetic materials research. However, spintronics requires hard magnets exhibiting small saturation magnetization and low spin relaxation. Mn-based alloys that are composed of Mn and light group III and/or group IV elements exhibit such properties and may belong to a new category of magnetic materials. In this article, we review the magnetic properties of Mn-based hard magnet films. In particular, we focus on low spin relaxation as a new viewpoint for hard magnets, and we discuss the origin of their extraordinary magnetism in terms of their unique electronic structures. Graphical abstract: